The Last Nationwide Smallpox Epidemic in the Netherlands: Infectious Disease and Social Inequalities in Amsterdam, 1870–1872. Issue 2 (17th November 2023) - Muurling, Sanne; Riswick, Tim; Buzasi, Katalin
Abstract: The complex relationship between the history of infectious diseases and social inequalities has recently attracted renewed attention. Smallpox has so far largely escaped this revived scholarly scrutiny, despite its century-long status as one of the deadliest and widespread of all infectious diseases. Literature has demonstrated important differences between rural and urban communities, and between cities, but has so far failed to address intra-urban disparities due to varying living conditions and disease environments. This article examines the last nationwide upsurge of smallpox in the Netherlands through the lens of Amsterdam's 50 neighborhoods in the period 1870–72. We use a mixed methods approach combining qualitative spatial analysis and OLS regression to investigate which part of the population was affected most by this epidemic in terms of age and sex, geographic distribution across the city, and underlying sociodemographic neighborhood characteristics such as relative wealth, housing density, crude death rate, and birth rate. Our analyses reveal a significant spatial patterning of smallpox mortality that can largely be explained by the existing social environment. Lacking universal vaccination, the smallpox epidemic was not socially neutral, but laid bare some of the deep-seated social and health inequalities across the city.